The Health Economic-Industrial Complex 4.0: for an integrated vision of economic, social, and environmental development - Gadelha, Carlos Augusto Grabois (Cadernos do Desenvolvimento, 2023)
COVID-19 pandemic is one of the most important phenomena of recent history. The current national and global context has dramatically revealed the correctness of the central hypothesis of HEIC research program, which indicates the endogenous, analytical and political interdependence between social and economic dimensions of development. In the light of the challenges presented by the current technological, economic, and social transformations intensified with the pandemic, this paper points to the need of political-theoretical boldness to overcome false and linear dichotomies and rethink development strategies. Finally, it suggests a new agenda for the HEIC research program, incorporating the challenges raised by the contemporary transformations and pointing out ways so that health and well-being are thought as possibilities to overcome the historical impasse of development, in a systemic and structural approach committed to economic dynamism, social needs, and nature.